2017
DOI: 10.1128/iai.00321-17
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia muridarum with Mutations in Chromosomal Genes tc0237 and/or tc0668 Is Deficient in Colonizing the Mouse Gastrointestinal Tract

Abstract: Chlamydiae colonize the gastrointestinal tracts of both animals and humans. However, their medical significance remains unknown. We have previously shown that wild-type Chlamydia muridarum spreads to and establishes stable colonization of the gastrointestinal tract following intravaginal inoculation. In the present study, we found that C. muridarum with mutations in chromosomal genes tc0237 and/or tc0668 was defective in spreading to the mouse gastrointestinal tract, which correlated with its attenuated pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…It is worth noting that deficiency in pGP3 reduced C. muridarum survival in the stomach by more than 100-fold, while the reduction in survival in the vagina was only ϳ8-fold. This discrepancy is consistent with previous observations that loss-of-function mutations in genes carried in the C. muridarum plasmid or genome caused a more dramatic phenotype in the GI tract than in the genital tract (28)(29)(30)53). The GI tract antimicrobial machineries, such as gastric acid and digestive hydrolases, are more robust than those in the genital tract.…”
Section: Fig 10supporting
confidence: 90%
See 1 more Smart Citation
“…It is worth noting that deficiency in pGP3 reduced C. muridarum survival in the stomach by more than 100-fold, while the reduction in survival in the vagina was only ϳ8-fold. This discrepancy is consistent with previous observations that loss-of-function mutations in genes carried in the C. muridarum plasmid or genome caused a more dramatic phenotype in the GI tract than in the genital tract (28)(29)(30)53). The GI tract antimicrobial machineries, such as gastric acid and digestive hydrolases, are more robust than those in the genital tract.…”
Section: Fig 10supporting
confidence: 90%
“…Recent studies have shown that vaginal C. muridarum can not only ascend to the oviduct but also spread to the GI tract (26) via a hematogenous route (27) to establish long-lasting colonization in the GI tract. Interestingly, this genital-to-GI-tract spreading seems to correlate with C. muridarum induction of hydrosalpinx in the genital tract (28)(29)(30). These observations have led to the proposal of a two-hit model partially explaining C. muridarum pathogenicity in the upper genital tract (7).…”
mentioning
confidence: 93%
“…C. trachomatis is naturally transmitted among humans sexually, while C. muridarum may be naturally transmitted among mice via the oral-fecal route (instead of sexually). This is because the C. muridarum plasmid or plasmid-encoded proteins or some chromosomal proteins have been shown to be more important for C. muridarum to colonize the GI tract than to infect the genital tract (47,48). In addition, the C. muridarum genome still maintains three copies of a full-length cytotoxin gene with significant homology to genes for large clostridial cytotoxins (49).…”
Section: Discussionmentioning
confidence: 99%
“…C. muridarum EBs were used to inoculate 6-to 7-week-old female mice (Jackson Laboratories, Inc., Bar Harbor, ME) intravaginally or intragastrically as described previously (10,20,26,48). The following mice were used in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…C. muridarum EBs were used to inoculate 6-to 7-week-old female mice (The Jackson Laboratory, Inc., Bar Harbor, ME) intravaginally as described previously (10,49,51,52). The mouse strains used in the current study included wild-type C57BL/6J mice (stock number 0006640; The Jackson Laboratory) and mice deficient in CD8 ϩ T cells, designated B6.129S2-Cd8a tm1Mak /J mice (stock number 002665; The Jackson Laboratory).…”
Section: Methodsmentioning
confidence: 99%